Congenital Microphthalmic Syndrome in a Swine. (21st June 2018) - Andrysikova, Radka; Sydler, Titus; Kümmerlen, Dolf; Pendl, Wolfgang; Graage, Robert; Moutelikova, Romana; Prodelalova, Jana; Voelter, Katrin
Abstract : A 17-week-old crossbred finishing pig was presented for lameness of approximately one week. Clinical evaluation, including ophthalmologic examination, revealed ataxia, partial flaccid paresis of the pelvic limbs, skin lesions at feet and claws, and severely reduced vision/blindness. Both eyes had multiple persistent pupillary membranes (iris-to-iris and iris-to-lens) and hypermature cataracts. Histopathological examination of the eyes revealed microphthalmia, microphakia with cataract formation, myovascularised membrane in the vitreous, retinal detachment, and retinal dysplasia. Microscopic examination of tissues collected postmortem demonstrated nonsuppurative polioencephalomyelitis with the most prominent inflammatory lesions in the lumbar spinal cord. Subsequently, presumed Teschen/Talfan disease was confirmed by porcine teschovirus identification in the spinal cord using the reverse transcription-polymerase chain reaction (RT-PCR). To the authors' knowledge, this is the first case report describing in detail histopathological changes in the porcine congenital microphthalmic syndrome.